Structure and Composition of Reptile Communities in Human Modified Landscape in Gianyar Regency, Bali - Ida Ayu Ari Janiawati; Mirza Dikari Kusrini; Ani Mardiastuti (HAYATI Journal of Biosciences, 2016)
As one of the centres of tourism in Bali, Gianyar Regency has undergone a rapid development rate which could threaten wildlife, including reptile community. This research was carried out in July to October 2014 to (1) analyse the reptile community on various gradients of human modified landscape, (2) determine the relationship between environmental character and reptiles, and (3) determine body size trend of generalist species along landscape gradient. Standard visual encountered surveys were used to observe reptile community in four human modified landscape (settlements, rice fields, farmland/cropland, and monoculture stands). We found 21 species of reptiles (n = 602 individuals) and the Shannon–Wiener index for diversity was 1.78. Reptile abundance tends to decline in increasing level of modification. Water sources and vegetation cover were positively correlated to reptile community, while disturbance factors (i.e. decrease in area size and shorter distance to settlements) give negative impact to reptile community. There was no correlation between body size of generalist species of reptile (Gekko gecko) and level of landscape modification.